Kapasitasi Kader Kesehatan tentang Posyandu Integrasi Layanan Primer berbasis Aplikasi SIPADU-ILP di Desa Talang Aur, Kecamatan Indralaya, Kabupaten Ogan Ilir - Siti, Siti Halimatul Munawarah; Budi, Iwan Stia; Najmah, Najmah; Tari, Putri Inrian (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: Posyandu cadres play a crucial role in supporting the implementation of the Integrated Primary Care (ILP) program as part of the transformation of community-based health services. However, limited knowledge and digital literacy among cadres have hindered the optimal implementation of Posyandu activities. This community service activity aimed to improve the knowledge and skills of Posyandu cadres in Talang Aur Village, Indralaya District, Ogan Ilir Regency through education, simulation, and mentoring using an information technology–based approach. Methods: The implementation consisted of three main stages: education, simulation, and mentoring, involving 50 Posyandu cadres as participants. Evaluation instruments included a pre–posttest to measure knowledge improvement and an application evaluation questionnaire to assess ease of use, usefulness, and user satisfaction. The activity was conducted on October 27, 2025, at the Talang Aur Village Hall. Results: The results showed a significant increase in the average knowledge score of cadres from 65.60 to 96.40 (p < 0.05), along with a high level of satisfaction regarding the ease of use and usefulness of the SIPADU-ILP (Integrated Posyandu Recording System for Primary Care Integration) application. Conclusion: This community service program proved effective in strengthening the competencies of Posyandu cadres, enhancing the efficiency of digital-based recording and reporting, and supporting the acceleration of community-based and information technology–driven primary health care transformation.